IMPLIKASI KEMAPANAN EKONOMI SEBAGAI KAFAAH DALAM PERNIKAHAN (Studi Kasus Masyarakat Kaliwates kab. Jember) - Harun Triyono; Ahyat Habibi (SAMAWA, 2025)
Economic stability, as part of the concept of kafaah, plays a vital role in establishing a harmonious and sustainable marriage from the perspective of Islam and the social reality of the Kaliwates community. This research employs a qualitative approach using a case study method through literature review and in-depth interviews with local residents. The findings reveal that scholars differ in their views regarding economic stability as an element of kafaah; the Hanafi and Hanbali schools consider it important, while the Shafi’i and Maliki schools do not require it strictly. The people of Kaliwates perceive economic stability as important, though it can be built together after marriage, provided there is communication, cooperation, and mutual commitment. They apply practical strategies such as joint business ventures, role-sharing, and mutual respect to maintain household harmony amid financial disparity. The study concludes that economic readiness supports family stability, even though it is not a requirement for the validity of marriage. Scientifically, this study contributes to strengthening the understanding of kafaah in the economic context and offers practical recommendations for prospective couples and the broader community in approaching marriage proportionally according to Islamic teachings. Keywords: economic, stability, kafaah, marriage